Modulation of Immunological Pathways in Autistic and Neurotypical Lymphoblastoid Cell Lines by the Enteric Microbiome Metabolite Propionic Acid - Frye, Richard E.; Nankova, Bistra; Bhattacharyya, Sudeepa; Rose, Shannon; Bennuri, Sirish C.; MacFabe, Derrick F. (Frontiers in Immunology, 2017)
Propionic Acid (PPA) is a ubiquitous short chain fatty acid which is a fermentation product of the enteric microbiome. While PPA has beneficial effects, it is also associated with human disorders, including autism spectrum disorders (ASD). We previously demonstrated that PPA modulates mitochondrial dysfunction differentially in a subsets of lymphoblastoid cell lines (LCLs) derived from patients with ASD. Specifically PPA significantly increases mitochondrial function in LCLs that have mitochondrial dysfunction at baseline (called AD-A LCLs) as compared to ASD LCLs with normal mitochondrial function (called AD-N LCLs) and control LCLs (CNT LCLs). PPA at 1mM was found to have a minimal effect on expression of immune genes in CNT and AD-N LCLs. However, as hypothesized, Panther analysis demonstrated that 1mM PPA exposure at 24hrs or 48hrs resulted in significant activation of the immune system genes in AD-A LCLs. When the effect of PPA on ASD LCL were compared to the CNT LCLs, both ASD groups demonstrated immune pathway activation, although the AD-A LCLs demonstrate a wider activation of immune genes. IPA analysis identified several immune related pathways as key Canonical Pathways that were differentially regulated, specifically human leukocyte antigen expression and immunoglobulin production genes were upregulated. These data demonstrate that the enteric microbiome metabolite PPA can evoke atypical immune activation in LCLs with an underlying abnormal metabolic state. As PPA, as well as enteric bacteria which produce PPA, have been implicated in a wide variety of diseases which have components of immune dysfunction, including ASD, diabetes, obesity and inflammatory diseases, insight into this metabolic modulator may have wide applications for both health and disease.